CONTEMPORARY TRENDS AND TOOLKIT OF COMPETITION ADVOCACY - Klymenko, Viktoriya (Proceedings of National Aviation University (archive), 2013)
The article summarizes international experience on contemporary forms of competition advocacy as part of competition policy, determines the major world trends of competition advocacy. A modern competition advocacy toolkit to competitive agencies and methods of evaluating the competition advocacy effectiveness are worked out.